(3GdeVGjbI aj ahGFJ GdUdhGJs - (3GdWGhSj, GdMSfj, CHh GdbGSe, QVi GdnqOjf, Ydj Hf ehSi Hf LYaQ Hf WGhhS, J (B664 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3Eeej PGcQ aj gPg GdChQGb HYV eG QhjJg ef GdGMGOjK aj JMbjb GdeVGSbI aj ahGFJ GdUdhGJ heG CJbdO GdMce HCMO Gdbhdjf Hd jYjf Pdc ef cda Hg (B...s
(3BNQgG (B:s
... (3Ke PcQ GdabgGA HcdGe Od Ydi Cfg eYJH Ydjge Ke CPf Ydjg GdSdGe (B... (3CdJeS GdeGA CJhVC Hg hCUdj eYg aGfJHgJ aj CKQ Pdc hUdi Gddg Ydi eMeO hBdg GdWGgQjfs
(3JHUQI GdYfhGf (B:s
(3ChQOgG aj eWdY MOjKg Yf GdehGSYI hGdeVGjbI HOhf JQbje bHd (B8713s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\26s
(3GdPQjYI (B23 - 138s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis